Sistem Informasi Kepegawaian Pada PT Graha Sriwijaya Sejahtera Sentosa - Angelica, Cornelia Okta; Rachmadi, Muhammad; Widi, Anugerah (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2024)
A personnel information system is a system that provides information about personnel to help companies manage employee data more easily and quickly. PT Graha Sriwijaya Sejahtera Sentosa is a company engaged in the distribution of car batteries under the Massiv brand. Problems that exist in companies include the accumulation of prospective employee application files resulting in the destruction of rejected employee application files, searching for employee data which takes a lot of time because employee data has to be searched in a storage cupboard so it is less efficient and employee leave applications are still recorded manually. in written media such as books and paper which have a fairly high risk of being lost or damaged, which causes data processing related to the company's human resource information system to still have shortcomings and inefficiencies. The system development method used is the RUP method (Rational Unified Process) by observing the running system. This research aims to collect data and convey information about employees. The results of interviews with the company's HRD revealed problems in collecting employee data adapted to the PIECES framework as welldiagram usecase as well as in planning to useclass diagram anddiagram activity andMySQL for database storage. The purpose of creating this system is to simplify the process of collecting personnel data in companies. Therefore, having a personnel information system in the company can help the company more easily collect employee data, provide information to employees regarding the company's internal affairs, and help employees more easily apply for leave without having to contact their superiors directly.